A inclusão de cláusula obrigatória de implementação de programa de integridade (compliance) nos acordos de colaboração premiada em crimes empresariais: um estudo de caso originado da Polícia Civil do Ceará - Sena, Giuliano Vieira (Universidade do Vale do Rio dos Sinos, 2024)
This dissertation deals with the inclusion of a mandatory clause for the implementation of an integrity program (compliance) in plea bargain agreements in investigations of corporate crimes, as recommended in article 4, paragraph III, of Law 12.850/2013. Its problem is: is the inclusion of a mandatory clause for the implementation of a compliance program adequate for the purposes of preventing corporate crimes? The methodology applied is an exploratory, qualitative and bibliographic study, seeking to associate theoretical-dogmatic, doctrinal and jurisprudential research and by through the use of participant observation, as a researcher, as a police officer and, based on his professional experience, enriching the work, following it more closely and generating social impact. In view of the above, the implementation of a mandatory clause for implementing an integrity program (compliance) in plea bargain agreements is appropriate for the purpose of preventing corporate crimes. The first chapter provides a historical overview of the expansion of business justice and the entire path taken to forge the institute of plea bargaining. The second chapter highlights the integrity program (compliance), its development and respective purposes, as well as its theoretical and normative framework. This is followed by the third chapter, which specifically reveals a practical case along the lines defended in this dissertation, with a detailed analysis of a criminal investigation led by the Civil Police of Ceará. Because of this, the subject is legally relevant, opening up new paths for combating crime not only by criminal prosecution agencies, but also at all levels of the company, especially at the top.
Keywords: Direito da empresa; Colaboração premiada; Cláusula obrigatória de Programa de integridade (compliance); Cláusula obrigatória; Crimes empresariais; Corporate law; Plea bargaining; Mandatory clause of an integrity program (compliance); Mandatory clause; Corporate crimes; ACCNPQ::Ciências Sociais Aplicadas::Direito